Effectiveness of Copper Nanoparticles in Wound Healing Process Using In Vivo and In Vitro Studies: A Systematic Review - Cristian Sandoval; Gemima Ríos; Natalia Sepúlveda; Jessica Salvo; Vanessa Souza-Mello; Jorge Farías (MDPI AG, 2022)
Chronic wounds are defined as wounds that do not heal in an orderly and timely manner through the various stages of the healing process. Copper nanoparticles are essential in dressings for wound healing because they promote angiogenesis and skin regeneration, which hasten the healing process. This systematic investigation sought to explain how copper nanoparticles affect chronic wound healing in vivo and in vitro. We realized a systematic review of original articles studying the effectiveness of copper nanoparticles in the healing process of chronic wounds. The protocol was registered in the PROSPERO database. Several databases were searched between 2012 and January 2022 for English-language papers using MeSH terms and text related to chronic wounds, copper nanoparticles, and wound healing. Quality was evaluated using National Institute for Health and Care Excellence methodology and PRISMA guidelines. We looked at a total of 12 primary studies. Quantitative data were gathered and presented in all studies. Our results suggest that copper nanoparticles could have an excellent healing property, facilitating the liberation of growth factors that help the anti-inflammatory process of the wound and significantly improving antibacterial and antioxidant activities. In addition, copper presents a higher biocompatibility than other metallic ions, promoting regeneration and increasing skin quality.